Effect of change management on operational excellence in the electrical and electronics industry - Oon, Fok Yew (2014)
Although the electrical and electronics (E&E) industry is the leading manufacturing sector in Malaysia, the industry’s share of all exports has decreased gradually during the last ten years. To compete in the marketplace, E&E organizations need to focus on making the most effective use of resources in their operations to ensure sustainability of growth. Such growth can be enhanced by having effective management of change (MOC) that employee commitment supports. The present study examines the relationship between six MOC elements (technology, structure, strategy, leadership, human resource & culture) and operational excellence (OPX) and employees’ affective commitment to change (ACTC) as a moderating variable. A survey of a sample of E&E manufacturing sector in Malaysia was conducted. Data were analyzed using multiple regression and hierarchical regression. The theoretical framework was guided by resource-based perspective. The analysis found significant, positive relationships between organic structure, operations strategy, transformational leadership style and human resource practices on achievement of OPX. The research had mixed findings, but supported the moderating effect of ACTC on relationship between the MOC and OPX. This study was limited because it was confined solely to the Malaysian E&E industry and suggests that future research could be conducted in other industries. The results of this study could promote a better understanding of the OPX in the E&E industry and its implications for activities concerning operational management and managing change, thus contributing to a wider body of knowledge. Success in change depends upon the proper integration of organic structure, operations strategy, transformational leadership style and human resource practices. Therefore, the recommendation to management is to establish policy, systems and processes by integrating both hard elements (structure & strategy) and soft elements (leadership & human resource) in strategic planning and future directions.